Formation and cleavage of 2-keto-3-deoxygluconate by 2-keto-3-deoxygluconate aldolase of Aspergillus niger. - Allam, A M (1975)
2-Keto-3-deoxygluconate aldolase of Aspergillus niger, an enzyme that has not been reported previously, was purified 468-fold. Maximal activity was obtained at pH 8.0 and 50 C. The enzyme exhibited relative stereochemical specificity with respect to glyceraldehyde. The Km values for 2-keto-3-deoxygluconate, glyceraldehyde, and pyruvate were 10, 13.3, and 3.0 mM, respectively. The effects of some compounds and inhibitors on enzyme activity were examined. Stability of the enzyme under different conditions was investigated. The equilibrium constant was about 0.33 X 10(-3) M.